2016
DOI: 10.1590/0104-6632.20160332s20150146
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN SOURCES ON TPOMW VALORIZATION THROUGH SOLID STATE FERMENTATION PERFORMED BY Yarrowia lipolytica

Abstract: -This manuscript reports the valorization of two-phase olive mill waste (TPOMW) as raw material and carbon source for solid state fermentation using Yarrowia lipolytica as biocatalyst. Due to its chemical characteristics, a combination of different raw materials (TPOMW and wheat bran, WB) was evaluated and two distinct nitrogen sources were applied as supplementation for lipase production. A TPOMW/WB ratio of 1:1 and supplementation with ammonium sulfate was chosen as the best condition. The productivity in 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
(53 reference statements)
1
8
0
1
Order By: Relevance
“…A similar effect was observed in the production of lipase by Bacillus coagulans in SSF of melon wastes, where the addition of (NH 4 ) 2 SO 4 increased enzyme production 1.6 times compared to urea addition, while other organic nitrogen sources had no effect [33]. Also, Lopes et al [34] found that the use of (NH 4 ) 2 SO 4 led to improve production of lipase by Yarrowia lipolytica in SSF of OP with WB when compared with the use of urea. The same positive effect of inorganic nitrogen was described by Lima et al [35] in the production of lipase by Penicillium aurantiogriseum in SmF.…”
Section: Effect Of Nitrogen Sourcessupporting
confidence: 63%
“…A similar effect was observed in the production of lipase by Bacillus coagulans in SSF of melon wastes, where the addition of (NH 4 ) 2 SO 4 increased enzyme production 1.6 times compared to urea addition, while other organic nitrogen sources had no effect [33]. Also, Lopes et al [34] found that the use of (NH 4 ) 2 SO 4 led to improve production of lipase by Yarrowia lipolytica in SSF of OP with WB when compared with the use of urea. The same positive effect of inorganic nitrogen was described by Lima et al [35] in the production of lipase by Penicillium aurantiogriseum in SmF.…”
Section: Effect Of Nitrogen Sourcessupporting
confidence: 63%
“…CCD-2 T9 treatment surpassed CCD-1 T22 in laccase activity, as well as specific activity at 72 h and 168 h of culture (T9, 6, 4. In Figure 4, it was observed too a change in slope was observed for enzyme activity and specific activity at 72 h. In addition, none of the response variables decreased, as was observed for CCD-1, suggesting (C/N) 0 ratio did not influence the result, since relatively higher nitrogen concentrations and lower (C/N) 0 ratios provide primary and secondary metabolite production [34,66].…”
Section: Central Composite Design-2 (Ccd-2)mentioning
confidence: 72%
“…The solid-state fermentation using the GRAS recognized Y. lipolytica and L. paracasei [ 6 , 13 ], the nutritional and functional values of the okara and pork lard [ 4 , 10 ], may be significantly improved [ 1 ] by generating bioactive peptides and organic acids including fatty acids with antimicrobial potential [ 3 ]. To the best of our knowledge, no information has been found in the literature about the conversion of both okara and pork lard through SSF fermentation using a co-culture of Y. lipolytica and L. paracasei .…”
Section: Discussionmentioning
confidence: 99%
“…Both Y. lipolytica and Lactobacillus spp. are used in the production of fermented products due to their generally recognized as safe (GRAS) status [ 6 , 13 ]. Fermentation using microorganisms in a co-culture such as LAB and yeast could provide promising results such as an increase in the microbial safety status of the products by reducing the potential spore forming microorganism [ 4 ] due to the production of organic acids and other inhibitory substances [ 3 ].…”
Section: Introductionmentioning
confidence: 99%